(untitled) (Argumentum, 2011)
While inheriting and discarding development theories with Euro-centrist elements, this paper endeavors to innovate the theory of being poor in institutional economics by proposing the hypothesis of the asymmetry of cost and benefit in the institutional structure. It reviews and analyses a common historical understanding: that cost-transferring is the intrinsic institutional cause of underdeveloped nations being poor during different stages in the development of capitalism. (Part Two will analyze the experience and intrinsic mechanism through which China avoids the ’developmental pitfall’ entrapping developing countries in general.)